A priming nudge targeting innovative farmers: A large-scale survey experiment - Douadia Bougherara; Léa Gosset; Raphaële Préget; Sophie Thoyer (PLoS ONE, 2026)
This article measures farmers’ innovativeness and the effectiveness of a priming nudge on their (stated) intention to adopt an innovation, namely the French “Low-carbon label” (LCL). The LCL is an innovative certification framework that provides farmers with a potential new “green business model,” enabling them to generate income through the sale of certified carbon credits earned by reducing their own greenhouse gas (GHG) emissions. Using 6,005 responses to an online survey with French farmers, we validate an original scale designed to measure farmers’ capacity to innovate and find that innovativeness is positively correlated with stated intention to adopt the LCL. We then evaluate with a randomized experiment included in the questionnaire the net impact of a priming nudge, defined as exposure to a lexical field designed to unconsciously activate psychological factors, and implemented here with references to innovation in order to target the most innovative farmers. We show that the nudge has no detectable impact on the surveyed sample: it neither increases adoption intentions among the most innovative farmers nor discourages the less innovative ones. This absence of effect leads us to discuss the effectiveness of nudges when trying to influence farmers’ high-stakes decisions.